2018
DOI: 10.12688/f1000research.16473.2
|View full text |Cite
|
Sign up to set email alerts
|

Using zebrafish larval models to study brain injury, locomotor and neuroinflammatory outcomes following intracerebral haemorrhage

Abstract: Intracerebral haemorrhage (ICH) is a devastating condition with limited treatment options, and current understanding of pathophysiology is incomplete. Spontaneous cerebral bleeding is a characteristic of the human condition that has proven difficult to recapitulate in existing pre-clinical rodent models. Zebrafish larvae are frequently used as vertebrate disease models and are associated with several advantages, including high fecundity, optical translucency and non-protected status prior to 5 days post-fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In intracerebral haemorrhage (ICH), macrophages play a role in the secondary post-stroke phase and represent a therapeutic target [304,305]. While mice have been the main model of choice to examine cerebral haemorrhage, zebrafish models also allow study of ICH [306][307][308]. Macrophages also monitor neuronal activity and impact neuronal structural remodelling in mice [309] and zebrafish [310], and thus may impact cerebral ECs indirectly via neurons.…”
Section: Non-endothelial Cells Required For Cerebrovascular Developmentmentioning
confidence: 99%
“…In intracerebral haemorrhage (ICH), macrophages play a role in the secondary post-stroke phase and represent a therapeutic target [304,305]. While mice have been the main model of choice to examine cerebral haemorrhage, zebrafish models also allow study of ICH [306][307][308]. Macrophages also monitor neuronal activity and impact neuronal structural remodelling in mice [309] and zebrafish [310], and thus may impact cerebral ECs indirectly via neurons.…”
Section: Non-endothelial Cells Required For Cerebrovascular Developmentmentioning
confidence: 99%
“…We recognise that zebrafish larvae are developing animals, and different disease mechanisms may exist in comparison to adult humans. However, we have shown that key characteristics associated with the pathological response to blood in the brain are apparently conserved between young fish and adult humans, suggesting they can be reliably used to model aspects of ICH [87,88].…”
Section: Zebrafish Modelsmentioning
confidence: 99%
“…In addition, as recovery rates are so rapid in zebrafish larvae as demonstrated by Crilly et al, it poses questions on how this may differ to recovery in adult humans. However, understanding these types of processes following ICH during development may provide clues into how we might consider recovering the aged human brain in the future [87].…”
Section: Zebrafish Modelsmentioning
confidence: 99%
“…Unlike more commonly used rodent models, ICH in bbh mutant zebrafish larvae can occur without the need for invasive surgical procedures and thereby mimic the spontaneous nature of the human condition more closely. We have previously characterized disease outcomes in the zebrafish bbh model which recapitulates key pathological outcomes observed in mammalian models and patients (Crilly et al, 2018(Crilly et al, , 2019. The secondary injury response in zebrafish larvae is identified by an increase in macrophage recruitment and activation within the head at 24 h post injury, whilst neutrophils are the most numerous leukocyte population at this developmental stage.…”
Section: Introductionmentioning
confidence: 96%